Kazakhstan : country gender assessment : May 2006 - Asian Development Bank. East and Central Asia Regional Department; Asian Development Bank. Regional and Sustainable Development Department (Country gender assessment : Kazakhstan, 2006)
Summary (s. vii-x).
Keywords: naiset : Kazakstan; köyhyys : Kazakstan; yhdenvertaisuus : Kazakstan; sosiaalinen muutos : Kazakstan